Estudio del procedimiento monitorio del COGEP para regular la extinción de la acción monitoria por prescripción e instituirla en el artículo 2415 del Código Civil - Valdiviezo Orellana, Oscar Mattia (2023)
This research work entitled "STUDY OF THE MONITORING PROCEDURE OF THE COGEP TO REGULATE THE EXTINCTION OF THE MONITORY ACTION BY PRESCRIPTION AND INSTITUTE IT IN ARTICLE 2415 OF THE CIVIL CODE", was carried out because, in article 2415 of the Civil Code, establishes the prescription time of executive and ordinary actions, but the time in which the monitoring actions prescribe is not stipulated, since for these actions the collection of debts can be demanded through documents that are not executive titles, therefore, These actions are not defined as executive or ordinary, which causes the principle of legal certainty established in article 82 of the Republic of Ecuador Constitution to be violated, which consists in the norm previously established in the law being applied as a basis in the decisions and pronouncements that the judges have at the time of administering justice, since, since there is no pre-established norm in our laws regarding the prescription of payment orders, these may have different criteria on those, and in this sense, there are those who consider that payment orders are regulated under the general rule of the prescription of legal actions and rights contained in the Civil Code and on the other hand, there are those who consider that the monitoring actions do not have prescription time due to anomie or lack of norm stipulated in the law, which generates a debate regarding this issue, however, in the present work I have investigated starting from the doctrine regarding the prescription in general, what is its purpose and how it could be considered to reform the Civil Code in its article 2415 so that the monitoring actions prescribe; all this based on comparative legislation such as that of Spain and Uruguay, in addition to the fact that two cases in our country are exposed in a considerate manner where the difference in criteria regarding the prescription of these monitoring actions is evident in their final decision; Surveys and interviews were also used with law professionals in free practice, as well as with specialists in civil procedure, who almost all of them state that there is no time in our legislation for judicial actions through payment procedure to prescribe, which corresponds to the basis to carry out a legal reform plan towards the Civil Code for this purpose and thus materialize the principle of legal certainty.